Fundraising Strategy in Increasing the Acquisition of ZISWAF Funds at BSI Maslahat Surabaya Representative Office - Muchammad Chafidz Muchlisin; Thayib (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Fundraising serves as the foundation for Amil Zakat Institutions in realizing the potential of ZISWAF in Indonesia. However, many Zakat Management Institutions are still not optimal in implementing effective fundraising strategies, resulting in a gap between potential and actual realization. Therefore, this study aims to analyze the fundraising strategies implemented by BSI Maslahat, Surabaya Representative Office, in increasing the collection of ZISWAF funds. This research employs a qualitative method with a case study approach through interviews, documentation, and observation. The results show that BSI Maslahat applies two main approaches in its fundraising strategy: Direct Fundraising and Indirect Fundraising, both conducted offline and online. Direct Fundraising includes zakat pick-up services, zakat collection partners (MPZ), zakat counters, as well as approaches through digital banking and crowdfunding applications. Meanwhile, Indirect Fundraising involves media campaigns, social events, donor services, and collaborations with media and strategic partners. The challenges faced include limited human resources, suboptimal mastery of fundraising products by staff, difficulty in accessing donor contacts from banking partners, and limitations in managing crowdfunding, which is still centralized.